L-sorbose production by acidotolerant acetic acid bacteria isolated from Thailand sources - Hanmoungjai W. (2014)
One hundred and twenty four isolates of acidotolerant acetic acid bacteria, isolated from various kinds of fruits and flowers collected in Chiang Mai, Thailand by an enrichmentculture approach were screened for their ability to produce rare ketose sugars. It was found that only 40 isolates (∼32%) could produce L-sorbose from sorbitol as detected by cysteinecarbazole reaction. This was then confirmed based on the thin layer chromatography technique. However, when analysed by HPLC, only twenty-two isolates were capable of producing L-sorbose. Of these, the strain CMU 48-1 produced highest accumulation of L-sorbose (0.629%), and was identified as Gluconacetobacter liquefaciens based on 16S rRNA gene sequence analysis. This is the first report of biotransformation of L-sorbose from sorbitol by Gluconacetobacter liquefaciens.